Ađđamiin or jolážiin – Sámi reindeer herders assessment of reindeer meat quality - Sara, Ravdna Biret Marja E.; Gaup Eira, Inger Marie (Septentrio Academic Publishing, 2021)
This study is based on knowledge systems and concepts about reindeer as food conducted from discussions with North Sámi elder reindeer herders in Guovdageaidnu, supplemented by written sources. 42 concepts were analyzed that represent the knowledge base and technical language of reindeer meat. Some key concepts are buoidi, ađđamiin and jolážiin, which reindeer herders use in the assessment process for reindeer meat quality. The word buoidi is over 2000 years old and is the foundation for Sámi reindeer herders’ reindeer meat quality assessment in Guovdageaidnu. The reindeer herder’s knowledge base and foundation of understanding has a holistic approach for assessment of reindeer meat quality. It starts already on the tundra assessing the herd and lasts until the meat is prepared and eaten. In the assessment of reindeer meat quality, there is an advanced and systematic knowledge system of meat quality, fat degree, fat content and fat extent that is articulated with the reindeer herder’s technical language through concepts in three dimensions: the live reindeer, carcass, and food. The assessment of reindeer meat quality has a long history of continuous use. The knowledge system can be used to raise awareness in other disciplines about how reindeer meat quality is traditionally assessed, and thus can bring new knowledge to public use and debate. Dás guorahalle máhttovuogádagaid ja doahpagiid mat gullet niestebohccui, nu movt Guovdageainnu vuorrasit boazosápmelaččat leat čilgen munnuide birgen- ja báikevuođu ságastallamiin ja maid letne viežžan čálalaš gálduin. 42 doahpaga analysa čájeha bohccobiergomáhttovuođu ja fágagiela. Muhtun doahpagat leat vuođđodoahpagat, dego buoidi, ađđamiin ja jolážiin, go boazosápmelaččat čilgejit bohccobierggu kvalitehta. Buoidi-sátni, mii lea badjel 2000 jagi boaris, vuođđuda Guovdageainnu boazosápmelaččaid bohccobiergokvalitehta árbevirolaš árvvoštallama. Boazodoalu máhttovuođus ja ipmárdusvuođus lea ollislaš ipmárdus, mii lea vuolggasadji árvvoštallat bohccobiergokvalitehta ...